Upregulation of PD-L1 and PD-L2 in neck node metastases of head and neck squamous cell carcinoma - Moratin, Julius; Safaltin, Ayse; Herpel, Esther; Hoffmann, Jürgen; Freier, Kolja; Heß, Jochen; Horn, Dominik (Head & neck, 2019)
Background This study aimed on evaluating the expression levels of the immune checkpoint proteins, PD-L1 and PD-L2, in tissue specimens of 175 oral squamous cell carcinomas (OSCC) and 33 corresponding lymph node metastases (LNM). Methods Tissue microarrays of primary OSCC and matched LNM were investigated via immunohistochemistry regarding PD-L1/PD-L2 expression. Results were compared for primary tumors and corresponding metastases and correlated with clinicopathological data. Results PD-L1 expression in cancer cells correlated significantly with tumor size, and the presence of regional metastases (P < 0.01). PD-L1 expression was significantly higher in metastases as compared to primary OSCC (P < 0.05). Overall survival was significantly worse in patients with higher levels of PD-L1 and PD-L2 score (P < 0.05). Conclusions This is the first publication to compare PD-L1 and PD-L2 expression in primary OSCC and matched LNM. The results indicate that anti-PD-1 therapy may be of therapeutic use even in early stage OSCC to prevent further progression.
Gesehen am 17.01.2020